Pregnancy after lung and heart–lung transplantation: a French multicentre retrospective study of 39 pregnancies - Bry, Charlotte (ERJ Open Res, 2019)
Pregnancy after lung and heart–lung transplantation remains rare. This French study deals with change in lung function after a pregnancy and the maternal and newborn outcomes. We retrospectively included 39 pregnancies in 35 women aged >20 years. Data on patients, course of pregnancies and newborns were collected from nine transplantation centres. Mean age at time of pregnancy was 28 years. Cystic fibrosis affected 71% of patients. Mean±sd time between transplantation and pregnancy was 63±44 months. 26 births occurred (67%) with a mean term of 36 weeks of amenorrhoea and a mean birthweight of 2409 g. Prematurity was observed in 11 cases (43%). Forced expiratory volume in 1 s was 83.9% of predicted before pregnancy and 77.3% of predicted 1 year after the end of pregnancy (p=0.04). 10 patients developed chronic lung allograft dysfunction after delivery. Nine patients died at a mean±sd time after transplantation of 8.2±7 years and a mean±sd time after pregnancy of 4.6±6.5 years. These data show that pregnancy remains feasible in lung and heart–lung transplant recipients, with more frequent maternal and newborn complications than in the general population. Survival in this cohort appears to be similar to the global survival observed in lung transplant recipients. Planned pregnancy and multidisciplinary follow-up are crucial.